The Influence of Internal and External Factors on Radiographer Compliance, and its Impact on the Implementation of Radiation Safety SOPS at Clinic X, Mecca, KSA - Wahyu HANANI; Erislan ERISLAN; Tatan SUKWIKA (PT Keberlanjutan Strategis Indonesia, 2025)
This study examines the problem of the influence of internal factors (knowledge, attitude, and work experience) on radiographer compliance and implementation of radiation safety SOPs, the influence of external factors (condition of equipment and facilities, and work safety culture) on radiographer compliance and implementation of radiation safety SOPs, the influence of radiographer compliance on the implementation of radiation safety SOPs, and the influence of internal and external factors on the implementation of radiation safety SOPs through radiographer compliance. The data collection method used a questionnaire with a Likert scale. Data analysis methods include descriptive statistical analysis, SEM-PLS analysis with outer model testing, inner model testing and hypothesis testing. The results of this study indicate that internal factors (knowledge, attitude, and work experience) have a positive and significant effect on radiographer compliance and implementation of radiation safety SOPs at the Radiology Unit of Clinic X, Mecca, KSA. External factors (condition of equipment and facilities, and work safety culture) have a positive and significant effect on radiographer compliance and implementation of radiation safety SOPs at the Radiology Unit of Clinic X, Mecca, KSA. Radiographer compliance has a negative and significant effect on the implementation of radiation safety SOPs at the Radiology Unit of Clinic X, Mecca, KSA. Internal and external factors have a significant influence on the implementation of radiation safety SOPs through radiographer compliance at the Radiology Unit of Clinic X, Mecca, KSA.